Costos de producción de porpagación de plántulas frutales (Citrícos) en viveros en la Provincia de Sucumbios Cantón Lago Agrio. - Chico Baño, Mónica del Pilar (2014)
This research was made, in order to analyze the profitability of a citrus nursery with seedlings because in the Lago Agrio Canton is lacking an establishment in which such seedlings are marketed. In Chapter I, was raised as General Objective: To determine the costs of production spread of citrus seedlings in the nursery, followed by the specific objectives were to determine the costs and revenues from the nursery to finally determine the profitability. In Chapter II, we consider the contribution of several authors in relation to the applied theme, starting with generalized concepts such as citrus (orange, lemon and grapefruit), its importance, and concepts of economic evaluation, which served as the basis for the development of this analysis. In Chapter III, is described in a detailed way all the resources that were used for this study, these were the same methods and research techniques such as relevance giving the survey and interview as a fundamental part of the investigation. In Chapter IV, the results of the research techniques applied and was the development of the specific objectives is to identify the costs of revenues and expenditures of the production process of citrus seedlings in nurseries are analyzed, then identified investment plan and ultimately the profitability of detailed analysis. In Chapter V, the conclusions of this study appropriately obtained based on research to finally give way to the recommendations set out. In Chapter VI, the literature cited survey forms and interviews indispensable for the development of the research is published